Love finds you in Humble, Texas - Higman, Anita (Love finds you., 2008)
Trudie Abernathy is a little inelegant, and she's never had much luck in love. To make matters worse, her thirtieth birthday is fast approaching and her sister, Lane, has decided to "treat" her to a makeover and a blind date. Trudie is about to protest, but then she meets the kind and devastatingly handsome Mason Wimberley. In spite of Trudie's humble manner, Mason finds her attractive, funny, and smart. But there's one obstacle in the way of the budding romance: Lane suddenly decides that she's in love with Mason! Trudie has never been one to compete with her glamorous sister, even when it means giving up the things she wants. Will she be able to stay true to her humble self and find her heart's desire in the process?